2013
DOI: 10.3233/asy-131181
|View full text |Cite
|
Sign up to set email alerts
|

Exponential stability for linear evolutionary equations

Abstract: We give an approach to exponential stability within the framework of evolutionary equations due to Picard [Math. Methods Appl. Sci. 32(14) (2009), 1768-1803]. We derive sufficient conditions for exponential stability in terms of the material law operator which is defined via an analytic and bounded operator-valued function and give an estimate for the expected decay rate. The results are illustrated by three examples: differential-algebraic equations, partial differential equations with finite delay and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…Waurick showed in [11] that as N → ∞, the sequence of solutions (u N ) N ∈N converges weakly in L 2 loc ([0, 1] × R) to u, the solution to the limit equation 1 2 ∂ 2 t u(ξ, t) + ∂ t u(ξ, t) + 1 2 u(ξ, t) − 2∂ 2 ξ u(ξ, t) = f (ξ, t) + ∂ t f (ξ, t), t ∈ R, subject to zero initial conditions and Neumann boundary on both ends. Furthermore, he showed that this limit admitted exponentially stable solutions in the sense of [10]. However, when the elliptic part, u N (ξ, t) − ∂ 2 ξ u N (ξ, t) = f (ξ, t), is replaced with the corresponding parabolic part, ∂ t u N (ξ, t) − ∂ 2 ξ u N (ξ, t) = f (ξ, t), the limit equation becomes 1 2 ∂ 2 t u(ξ, t) + ∂ t u(ξ, t) − 2∂ 2 ξ u(ξ, t) = f (ξ, t) + ∂ t f (ξ, t), t ∈ R, subject again to zero initial conditions and Neumann boundary.…”
Section: Possible Future Directionsmentioning
confidence: 99%
“…Waurick showed in [11] that as N → ∞, the sequence of solutions (u N ) N ∈N converges weakly in L 2 loc ([0, 1] × R) to u, the solution to the limit equation 1 2 ∂ 2 t u(ξ, t) + ∂ t u(ξ, t) + 1 2 u(ξ, t) − 2∂ 2 ξ u(ξ, t) = f (ξ, t) + ∂ t f (ξ, t), t ∈ R, subject to zero initial conditions and Neumann boundary on both ends. Furthermore, he showed that this limit admitted exponentially stable solutions in the sense of [10]. However, when the elliptic part, u N (ξ, t) − ∂ 2 ξ u N (ξ, t) = f (ξ, t), is replaced with the corresponding parabolic part, ∂ t u N (ξ, t) − ∂ 2 ξ u N (ξ, t) = f (ξ, t), the limit equation becomes 1 2 ∂ 2 t u(ξ, t) + ∂ t u(ξ, t) − 2∂ 2 ξ u(ξ, t) = f (ξ, t) + ∂ t f (ξ, t), t ∈ R, subject again to zero initial conditions and Neumann boundary.…”
Section: Possible Future Directionsmentioning
confidence: 99%
“…However, we provide an alternative proof, allowing to drop one constraint on the operator M imposed in [4]. We emphasize that due to the abstract structure of (1), our results apply to a broad class of differential equations, such as differential-algebraic equations, integro-differential equations or delay differential equations (see [4] for several applications). Throughout, let H be a complex Hilbert space with inner product ·|· and induced norm | · |.…”
Section: Introductionmentioning
confidence: 95%
“…[3]). We want to address the exponential stability of problems of the form (1), where A is a linear maximal monotone (or m-accretive) operator on some Hilbert space H and give sufficient criteria for the exponential stability in terms of the operator M. This was already done by the author in [4]. However, we provide an alternative proof, allowing to drop one constraint on the operator M imposed in [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that M(∂ t,µ ) is realised as a densely defined operator acting from L 2 µ (R; K) to L 2 µ (R; H) for all µ > ν. By[27, Lemma 3.6], for f ∈ dom(M(∂ t,µ ))∩dom(M(∂ t,η )) we have M(∂ t,µ )f = M(∂ t,ν )f.…”
mentioning
confidence: 99%